1997
DOI: 10.1111/j.1399-6576.1997.tb04652.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative metoprolol improves cardiovascular stability and reduces oxygen consumption after thoracotomy

Abstract: We found that preoperative beta-blockade during combined general anaesthesia and high thoracic epidural blockade stabilised perioperative HR and CI and decreased total oxygen consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 20 publications
0
15
1
1
Order By: Relevance
“…We excluded 40 trials-36 of which did not evaluate outcomes of interest, one that was a small subgroup analysis from a larger non surgical cohort, 18 and three that were multiple publications from the same dataset [19][20][21] -leaving 33 trials that fulfilled our inclusion criteria. …”
Section: Resultsmentioning
confidence: 99%
“…We excluded 40 trials-36 of which did not evaluate outcomes of interest, one that was a small subgroup analysis from a larger non surgical cohort, 18 and three that were multiple publications from the same dataset [19][20][21] -leaving 33 trials that fulfilled our inclusion criteria. …”
Section: Resultsmentioning
confidence: 99%
“…30 – 37 Twenty eight major perioperative cardiovascular events occurred among the 589 patients randomised to β blocker treatment, compared with 55 among the 563 patients randomised to placebo or standard care (relative risk 0.44, 0.20 to 0.97, 0.16 to 1.24). Moderate heterogeneity existed across the trial results (I 2 = 42%).…”
Section: Resultsmentioning
confidence: 99%
“…We excluded nine studies which reported only major cardiovascular complications within 30 days of surgery [1,2,[21][22][23][24][25][26][27] and a further nine studies which did not present data on perioperative myocardial ischaemia [28][29][30][31][32][33][34][35][36].…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of peri-operative cardiovascular complications in intermediate-risk patients, and the reports relating to higher cardiac risk patients If we examine the ARR of all the beta-blocker studies which report major cardiovascular complications, the ARR is 5.4% for major cardiovascular complications and 7.9% for myocardial ischaemia [1,2,[21][22][23][24][25][26][27]. Interestingly, this is lower than the ARR of 10.9% in perioperative myocardial ischaemia reported in this analysis of intermediate-risk patients.…”
Section: B M Biccardmentioning
confidence: 99%